The Readiness of The Cirebon City Government to Enter The Digital Economy Era in an ICT Perspective - A Al Hilmi, M; Guntoro, M; Sumardiono, A (Proceeding Interuniversity Forum for Strengthening Academic Competency, 2019)
The rapid globalization accompanied by democratization and the development of information and communication technology (ICT) pushes government institutions to use ICT in order to improve government public services, especially in the economic field. This research discussed the Cirebon City Government’s preparation to launch the Smart City Program planned from May 2017 for facing the development of ICT, particularly in smart economic sector. The research used qualitative and quantitative approaches elaborated by SWOT analysis to measure the readiness of the Cirebon City Government to enter the digital economy era. In addition, the level of the Cirebon City Government’s readiness was observed from the numbers of online shops and products managed by Cirebon citizens in online marketplace. The result showed that the Cirebon City Government and the citizens were in the early stages of entering the digital economy era in which it was proved through the existence of a basis/design of Local Regulations, community service products, and the design of the system integration of the Cirebon City that had led to the Smart City Concept.